"We are not worthy" – understanding why patients decline pulmonary rehabilitation following an acute exacerbation of COPD. (10th July 2014) - Harrison, Samantha Louise; Robertson, Noelle; Apps, Lindsay; C. Steiner, Michael; Morgan, Mike D. L.; Singh, Sally J.
Abstract: Purpose : To explore how patients who refuse referral to Pulmonary Rehabilitation (PR) appraise acute exacerbations of Chronic Obstructive Pulmonary Disease (COPD), in the context of having considered and declined PR. Method : Six participants recently hospitalized with an acute exacerbation COPD who refused a referral to PR subsequent to hospital discharge participated in in-depth interviews. Transcripts were subjected to Interpretative Phenomenological Analysis (IPA). Results : Three conceptual themes emerged comprising: "Construction of the self", reflecting the impact of the acute exacerbation on personal identity; "Relinquishing control", describing participants" struggle to maintain agency following an acute event; and "Engagement with others", embodying participants' sensitivity and responsiveness to interactions with others. Conclusions : Prominent in theses participants' narratives are self-conscious cognitions which appear founded in shame and stigmatization. These cognitions seem to reflect challenges to self-worth and appear associated with reduced help-seeking and isolation. Perceived personal culpability for COPD appears to sensitize participants' towards their interactions with health care professionals, construed as critical and judgmental which may increase avoidant behaviors, such as refusal of PR. When introducing PR, professionals should be aware of such sensitivities and facilitate open discussion which offers, time, compassion and understanding as a means of facilitating uptake. Implications for Rehabilitation: Patients who decline referral to Pulmonary Rehabilitation report self-conscious cognitions (i.e. shame, guilt, fear of others evaluation) associated with lowered self-worth and reduced help-seeking. When introducing Pulmonary Rehabilitation health care professionals need to be mindful of patients' sensitivities to being shamed which stem from perceived culpability for COPD. Professionals should facilitate an open discussion with patients which offers, time, compassion and understanding as a means of facilitating Pulmonary Rehabilitation uptake. Compassion focused interventions which encourage trust and safety may promote active partnership working and facilitate engagement in Pulmonary Rehabilitation.